Computational intelligence - Ruano, Antonio (2013)
The Centre for Intelligent Systems (CIS) is a multidisciplinary research and development centre, founded in 2001, in a very young university, the University of Algarve, in the south of Portugal. The centr's mission is to promote fundamental research in Computational Intelligence (CI) methodology.